Pediatric Musculoskeletal Trauma: Upper Limb - Restrepo, Ricardo; Cervantes, Luisa Fernanda; Zahrah, David; Schoenleber, Scott; Lee, Edward Y. (Seminars in Musculoskeletal Radiology, 2021)
Pediatric upper extremity injuries, acute and chronic due to overuse, are commonly encountered in the clinical setting. However, interpretation of imaging studies is often challenging in pediatric patients because of changing postnatal skeletal development and the broad spectrum of pathology that can potentially occur. This article discusses normal skeletal development and the pathomechanics of skeletal injuries in pediatric patients. It also outlines a framework for imaging as it pertains to the pediatric upper extremity, with specific emphasis on acute and chronic injuries to the shoulder, elbow, forearm, and wrist.
Keywords: shoulder; elbow; wrist; fracture; injury